Generation of T follicular helper cells in vitro: requirement for B‐cell receptor cross‐linking and cognate B‐ and T‐cell interaction. Issue 2 (9th October 2017) - Kolenbrander, Anne; Grewe, Bastian; Nemazee, David; Überla, Klaus; Temchura, Vladimir
Summary: The minimum requirements for in vitro modelling of natural CD4 + T‐cell differentiation into T follicular helper (Tfh) cells are still under investigation. We co‐cultured wild‐type and T‐cell receptor (TCR) transgenic CD4 + T cells from naive mice with dendritic cells and B‐cell receptor (BCR) transgenic B cells in the presence of HIV‐derived virus‐like particles containing matched B‐cell and T‐cell epitopes. This co‐culturing induced co‐expression of Tfh‐master regulator transcription factor BCL‐6 and CXCR5 in up to 10% of the wild‐type and up to 40% of the TCR‐transgenic CD4 + T cells. Phenotypic markers, production of interleukin‐21 and isotype switching of the B cells to IgG1 further indicated a helper function of the induced Tfh cells in vitro . Dendritic cells supported the generation of functional Tfh cells, but were unable to induce them without cognate B cells. Hence, our study presents a robust experimental system for efficient generation of functionally active Tfh cells in vitro and confirms the importance of cognate B‐ and T‐cell cross‐talk for the Tfh differentiation process. Abstract : Co‐culturing of T‐cell receptor transgenic CD4 + T cells with B‐cell receptor transgenic B cells in the presence of HIV‐derived virus‐like particles containing both cognate B‐ and T‐cell epitopes resulted in generation of BCL6 +  CXCR5 +  CD4 + T follicular helper (Tfh) cells. Dendritic cells supported this in vitro generation, but were unable to induce Tfh development without cognate B cells.